Investigating the Determinants of Eco-Friendly Purchase Intention among Malaysian Consumers in the Food and Beverage Industry - Yee Huei Lok; Fatin Hazimah Mohd Hasri; Felix Frall Anak Draman; Fifi Ellia Najwani Mesuan; Tew Chin En Fion; Rahul Mayur; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
The global shift toward sustainability has greatly influenced consumer behavior, particularly within Malaysia’s growing food and beverage (FB) sector. Yet, a persistent gap remains between consumers’ eco-friendly behavior and their actual purchasing decisions. This study investigates the determinants of eco-friendly purchase intention among Malaysian consumers in the FB industry, focusing on environmental concern, environmental knowledge, and perceived consumer effectiveness (PCE). A quantitative research design was employed using an online survey administered to 200 Malaysian consumers. The findings reveal that all three variables exert a significant positive influence on eco-friendly purchase intention, with environmental knowledge emerging as the strongest predictor. The findings provide valuable practical insights into the key determinants influencing Malaysian consumers’ purchase intention toward eco-friendly FB products. The result can assist FB industry in creating effective marketing strategies that promote sustainability while guiding consumers toward environmentally responsible purchasing decisions.